1015 cm−3 eV−1 level detection of density of states of a p-type polymer by hν-dependent high-sensitivity ultraviolet photoemission spectroscopy. (28th December 2016) - Sato, Tomoya; Kinjo, Hiroumi; Yamazaki, Junki; Ishii, Hisao
Abstract: We propose a method, called h ν-dependent high-sensitivity ultraviolet photoemission spectroscopy, to observe the density of states (DOS) in a very wide range from HOMO to extremely weak gap states (10 22 to 10 15 cm −3 eV −1 in density of states). The method was applied to a p-type semiconducting polymer. A series of spectra for h ν = 4.4–7.7 eV were recorded, and the DOS was obtained by overlapping the spectral part with a similar line shape between adjacent photon energy spectra to eliminate the photon energy dependence of the photoionization cross section. This method can be applied to both organic and inorganic materials, providing useful information about the DOS of functional materials.